Correlation of Sedentary Behavior and Sleep Duration with Visuospatial Memory in Early Children - Shidqi Maulida; Sultoni, Kuston; Ugelta, Surdiniaty (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
Sedentary behavior and sleep duration are indicated as contributors to the emergence of health problems. Especially in early children's cognitive function abilities, including nerve signal abilities, concentration levels and memory. So this research was carried out with the aim of exploring how much sedentary behavior and sleep duration are related to cognitive function (visuospatial memory) in early childhood. The quantitative correlation test is used to test how much the relationship both of variable. The research subjects were 45 children aged 4 years in Bandung city, West Java. The instruments used in data collection were the Accelerometer Actigraph GT3X and the Early Years Toolbox (Mr.Ant). The results of research data analysis stated that there was a significant relationship between sedentary behavior and visuospatial memory, p=.047 with a correlation coefficient of -.514. Sleep duration is related to cognitive function with a value of p = .028 and a correlation coefficient value of .360. The duration of sedentary behavior carried out by young children in daily life is negatively correlated with cognitive function, while the duration of sleep is positively correlated with cognitive function.